Formation and Characterization of [BrC(NMe2)2)][Br3] and [BrC(NMe2)2)]2[Br8] in Ionic Liquids. Issue 1 (2nd December 2016) - Sonnenberg, Karsten; Pröhm, Patrick; Steinhauer, Simon; Wiesner, Anja; Müller, Carsten; Riedel, Sebastian
Abstract : The polybromide salts [BrC(NMe2 )2 ]2 [Br8 ] and [BrC(NMe2 )2 ][Br3 ] were synthesized in the ionic liquid [BMP][OTf] (1‐butyl‐1‐methyl‐pyrrolidinium triflate). The compounds were characterized by Raman, NMR, and X‐ray single crystal structure determination as well as quantum‐chemical calculations. The polybromide dianion [Br8 ] 2– structure shows similarities to the very recently reported structure of the first octachloride [Cl8 ] 2– . Abstract :